2017
DOI: 10.1080/03004430.2016.1273909
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of staff–child interaction in 1–3-year-olds’ risky play in early childhood education and care

Abstract: Despite increased interest in children's risk-taking in play, little is known of this aspect considering children under three years. Therefore, this study aimed to investigate the concept of scaffolding to potentially describe patterns in staff-child interaction in 1-3-year-olds' risky play. Empirical data were taken from an exploratory study, executed as a focused ethnography with multiple data collecting techniques, resulting in a sample of 198 instances of risky play. Findings indicate that scaffolding is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 57 publications
3
10
0
2
Order By: Relevance
“…However, high-quality kindergartens have the potential to reduce this gap before formal schooling. Overall, our findings, together with recent previous research (see, for example, Bjørnestad and Os, 2018;Kleppe, 2017;Lekhal et al, 2013), may indicate that there is still untapped potential in Norwegian kindergartens.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…However, high-quality kindergartens have the potential to reduce this gap before formal schooling. Overall, our findings, together with recent previous research (see, for example, Bjørnestad and Os, 2018;Kleppe, 2017;Lekhal et al, 2013), may indicate that there is still untapped potential in Norwegian kindergartens.…”
supporting
confidence: 83%
“…However, as part of his investigation into staff-child interactions among one-to three-year-olds during risky play in Norwegian kindergartens, Kleppe (2017) found that on occasions where staff were present, they did not interact with children for 41% of these occasions. Based on this, the current research aims to supplement Kleppe's findings.…”
Section: Introductionmentioning
confidence: 99%
“…When the literature on five factors in the developed scale is examined; regarding the "Pro-beliefs and Supporting Children" factors, there are many studies that accept that risky play positively affects all areas of development of children and that children should be given the opportunity to play risky games (Gill, 2007;Ball, 2002;Sandseter, 2007;Sandseter, 2009a,b;Little, Wyver and Gibson, 2011;Brussoni, Olsen, Pike and Sleet, 2012;Little, Sandseter and Wyner, 2012;Sandseter, 2014;Little, 2015;Coe, 2017;Harper, 2017;Nikiforidou , 2017;Ünüvar and Kanyılmaz, 2017;Brussoni, Ishikawa, Han, Pike, Bundy, Faulkner and Masse, 2018;Kleppe, 2018;McFarland and Laird, 2018). However, regarding the "Feeling Anxiety and Distinguishing Risky Behaviors" factors; Cevher Kalburan (2014) reported that parents deprived their children of risky games due to their anxiety that their children could be injured, while Ball (2002) reported that parents put restrictions on risky play due to safety concerns.…”
Section: Resultsmentioning
confidence: 99%
“…Current studies in the literature emphasized the importance of children playing in natural environments and focused on the importance of playing risky play after taking safety measures in these environments. In particular, studies conducted in recent years have focused on the positive consequences and benefits for children rather than the dangerous and damaging consequences of risk play (Sandseter, 2007;Sandseter, 2009 (a, b); Little, Wyver and Gibson, 2011;Brussoni, Olsen, Pike and Sleet, 2012;Little, Sandseter and Wyner, 2012;Sandseter, 2014;Brussoni et al, 2015;Little, 2015;Güler and Iron, 2016;Brussoni, Ishikawa, Brunelle and Herrington, 2017;Coe, 2017;Harper, 2017;Nikiforidou, 2017;Ünüvar and Kanyılmaz, 2017;Brussoni, Ishikawa, Han, Pike, Bundy, Faulkner and Mâsse, 2018;Kleppe, 2018;McFarland and Laird, 2018). In this study, a scale development study was conducted in order to determine the opinions of parents about why they do not allow their children to be engaged in risky plays or how much they allow them.…”
Section: Introductionmentioning
confidence: 99%
“…Hvis vi antar at spenning og litt risiko fungerer som motivasjon for å vaere fysisk aktiv, kan manglende tilrettelegging handle om barnehageansattes manglende kunnskap eller negative holdninger til risikofylt lek. Tidligere studier viser riktignok at norske barnehageansatte er positive til barns utfoldelse og risikotaking i lek (Little et al, 2012;New et al, 2005), også med de aller yngste barna (Kleppe, 2017), men når man ser på utviklingen over tid, er det tegn på at også norske barnehageansatte har blitt mer fokuserte på sikkerhet i tråd med samfunnsutviklingen generelt (Sandseter & Sando, 2016). For barnehageansatte er balansen mellom å forhindre alvorlige skader og samtidig støtte erfaring med risikofylt lek på ingen måte en teoretisk diskusjon.…”
Section: Mulige Hindringer For Risikofylt Lekunclassified